Preparation of poly(vinyl alcohol)/poly(lactic acid)/hydroxyapatite bioactive nanocomposites for fused deposition modeling. (8th November 2017) - Wu, Jintian; Chen, Ning; Bai, Feng; Wang, Qi
Abstract : Poly(vinyl alcohol)/hydroxyapatite (PVA/HA) has excellent mechanical properties and osteoconductivity that allow it to be used for cartilage repair. However, nanofillers, such as HA, cause PVA to foam during the extrusion process, making it difficult to produce filament feedstocks with uniform diameters that are suitable for fused deposition modeling (FDM). In this article, a novel method was developed to prevent the foaming of PVA‐based nanocomposites during extrusion by selectively distributing HA in the poly(lactic acid) (PLA) phase. To achieve this, HA was treated with 3‐Glycidoxypropyltrimethoxysilane (KH560). The results showed that HA treated with KH560 was segregated from the PVA phase, thus preventing the foaming of PVA. Finally, filament feedstocks with a uniform diameter of 1.75 ± 0.05 mm, which is suitable for FDM, were successfully fabricated. Meanwhile, a mathematical equation for characterizing the printability of feedstock materials was improved. The results indicated that in combination with PLA, composites with a higher compressive modulus and better melt flowability were able to be processed by FDM. Finally, complex PVA‐based bioactive nanocomposite scaffolds with high dimensional accuracy, good mechanical properties, and biocompatibility were fabricated by the FDM machine. POLYM. COMPOS., 39:E508–E518, 2018. © 2017 Society of Plastics Engineers